How to mislead with statistics. Issue 4 (28th July 2021) - Lum, Kristian; Kabir, Naim; Bak‐Coleman, Joe
Abstract : Lessons from recent attempts to subvert the US election with data analysis. By Kristian Lum, Naim Kabir and Joe Bak‐Coleman Abstract : Lessons from recent attempts to subvert the US election with data analysis. By Kristian Lum, Naim Kabir and Joe Bak‐Coleman.